The role of Emotional Intelligence for success in motorsports - Christof Falch (Journal of Applied Leadership and Management, 2013)
What is the role of emotional competencies for success in motorsports. Is there a difference between the emotional competencies of race car drivers and the competencies of the normal population? Is there also a difference in the emotional competencies between successful and unsuccessful drivers?
Keywords: 650; emotional intelligence; emotional competencies